(untitled) (Chittagong University Journal of Biological Sciences, 2024)
This investigation describes the morpho-molecular characterization of the pathogen associated with infected leaf and fruits of tomato (Solanum lycopersicum L.). The fungal pathogen was identified based on their cultural morphology, microscopic features and analysis of Internal Transcribed Spacer (ITS) region sequences of nuclear ribosomal DNA (nrDNA). Cultural morphology including colour of the young and mature colony, growth pattern, concentric rings etc. and microscopic features including shape and size of microconidia, macroconidia, phialide, shape of apical and basal cells of macroconidia, septation in conidia, inter-septal distance and formation of chlamydospores corroborated the identity with the pathogenic fungi Fusarium oxysporum. The phylogenetic analysis based ITS regions sequences of nrDNA of the fungal isolate showed 100% identity with Fusarium oxysporum. Thus the ITS of nrDNA sequences validated the morphological data. Pathogenicity test also reconfirmed the identity of the test isolate of Fusarium oxysporum. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):31-40, 2020.